Modeling Analysis and Simulation Verification for Drive Tooth Stress of Rubber Track Wheel - Zihan Zhao; Xihui Mu; Fengpo Du; Jianhua Guo (Jixie chuandong)
The rubber track wheel generally transmits power by the engagement of the driving teeth of the rubber track and the driving pin of the driving wheel. The driving teeth are likely to be destroyed when they are subjected to excessive load or load impact. The mathematical model and calculation analysis for the driving tooth stress distribution are carried out. Firstly，based on structure parameters and transmission principle，the drive tooth profile equation is established and determining mapping parameters by the improved Powell algorithm. The optimization results show that the accuracy of the mapping tooth profile obtained by this method is 0.12%，which effectively improves the mapping accuracy. Secondly，based on the complex function method， the mathematical model for stress and deformation is established，and the stress distribution laws under different meshing positions are analyzed. Finally，the calculation conditions are set as boundary conditions，and the analysis results are verified by using Abaqus software. The simulation results show that the maximum error between the simulation data and the calculation data is about 11.76%，so the mathematical model can be applied to the analysis of the driving tooth stress. This calculation results can provide theoretical basis for structural optimization of driving teeth and improvement of local rubber materials.